Global Financial Regulatory Reform : Implications for Latin America and the Caribbean (LAC) - Rennhack, Robert (IMF Staff Position Notes; Staff Position Note ;, 2009)
The Latin America and Caribbean (LAC) region has weathered the global financial crisis reasonably well so far, although tighter global financial conditions began to take their toll on trade, capital flows and economic growth in late 2008. This resilience reflects the reforms put in place by many countries over the past decade to strengthen financial supervision and adopt sound macroeconomic policies. Building on this progress, the region's financial sector reform agenda now aims at further improvements, including steps aiming to improve compliance with the Basel Core Principles of Banking Supervision and to broaden and deepen domestic financial markets.